After-gate attack on a quantum cryptosystem - Wiechers, C.; Lydersen, L.; Wittmann, C.; Elser, Dominique Alexander; Skaar, Johannes; Marquardt, Christoph; Makarov, V.; Leuchs, Gerd (New Journal of Physics, 2011)
We present a method to control the detection events in quantum key distribution systems that use gated single-photon detectors. We employ bright pulses as faked states, timed to arrive at the avalanche photodiodes outside the activation time. The attack can remain unnoticed, since the faked states do not increase the error rate per se. This allows for an intercept-resend attack, where an eavesdropper transfers her detection events to the legitimate receiver without causing any errors. As a side effect, afterpulses, originating from accumulated charge carriers in the detectors, increase the error rate. We have experimentally tested detectors of the system id3110 (Clavis2) from ID Quantique. We identify the parameter regime in which the attack is feasible despite the side effect. Furthermore, we outline how simple modifications in the implementation can make the device immune to this attack. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, Bettina; Elser, Dominique Alexander; Bartley, Tim; Sabuncu, Metin; Wittmann, Christoffer; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2010)
We investigate the properties of an atmospheric channel for free space quantum communication with continuous polarization variables. In our prepare-and-measure setup, coherent polarization states are transmitted through an atmospheric quantum channel of 100 m length on the flat roof of our institute's building. The signal states are measured by homodyne detection with the help of a local oscillator (LO) which propagates in the same spatial mode as the signal, orthogonally polarized to it. Thus the interference of signal and LO is excellent and atmospheric fluctuations are auto-compensated. The LO also acts as a spatial and spectral filter, which allows for unrestrained daylight operation. Important characteristics for our system are atmospheric channel influences that could cause polarization, intensity and position excess noise. Therefore we study these influences in detail. Our results indicate that the channel is suitable for our quantum communication system in most weather condition
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.optik.1optik.atmosp

Attacks on practical quantum key distribution systems (and how to prevent them) - Jain, Nitin; Stiller, Birgit; Khan, Imran; Elser, Dominique Alexander; Marquardt, Christoph; Leuchs, Gerd (Contemporary Physics, 2016)
With the emergence of an information society, the idea of protecting sensitive data is steadily gaining importance. Conventional encryption methods may not be sufficient to guarantee data protection in the future. Quantum key distribution (QKD) is an emerging technology that exploits fundamental physical properties to guarantee perfect security in theory. However, it is not easy to ensure in practice that the implementations of QKD systems are exactly in line with the theoretical specifications. Such theory–practice deviations can open loopholes and compromise security. Several such loopholes have been discovered and investigated in the last decade. These activities have motivated the proposal and implementation of appropriate countermeasures, thereby preventing future attacks and enhancing the practical security of QKD. This article introduces the so-called field of quantum hacking by summarising a variety of attacks and their prevention mechanisms.
CRIS-Team Scopus Importer:2021-06-29
Keywords: countermeasures; practical data security; quantum computer; Quantum cryptography; quantum hacking; quantum key distribution

Depolarized guided acoustic wave Brillouin scattering in hollow-core photonic crystal fibers - Zhong, Wenjia; Stiller, Birgit; Elser, Dominique Alexander; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2015)
By performing quantum-noise-limited optical heterodyne detection, we observe polarization noise in light after propagation through a hollow-core photonic crystal fiber (PCF). We compare the noise spectrum to the one of a standard fiber and find an increase of noise even though the light is mainly transmitted in air in a hollow-core PCF. Combined with our simulation of the acoustic vibrational modes in the hollow-core PCF, we are offering an explanation for the polarization noise with a variation of guided acoustic wave Brillouin scattering (GAWBS). Here, instead of modulating the strain in the fiber core as in a solid core fiber, the acoustic vibrations in hollow-core PCF influence the effective refractive index by modulating the geometry of the photonic crystal structure. This induces polarization noise in the light guided by the photonic crystal structure.
CRIS-Team Scopus Importer:2021-06-29

Device Calibration Impacts Security of Quantum Key Distribution - Jain, Nitin; Wittmann, Christoffer; Lydersen, Lars; Wiechers, Carlos; Elser, Dominique Alexander; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review Letters, 2011)
Characterizing the physical channel and calibrating the cryptosystem hardware are prerequisites for establishing a quantum channel for quantum key distribution (QKD). Moreover, an inappropriately implemented calibration routine can open a fatal security loophole. We propose and experimentally demonstrate a method to induce a large temporal detector efficiency mismatch in a commercial QKD system by deceiving a channel length calibration routine. We then devise an optimal and realistic strategy using faked states to break the security of the cryptosystem. A fix for this loophole is also suggested. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Enhanced free space beam capture by improved optical tapers - Bartley, Tim; Heim, Bettina; Elser, Dominique Alexander; Sych, Denis; Sabuncu, Metin; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (2010)
In our continuous variable quantum key distribution (QKD) scheme, the homodyne detection set-up requires balancing the intensity of an incident beam between two photodiodes. Realistic lens systems are insufficient to provide a spatially stable focus in the presence of large spatial beam-jitter caused by atmospheric transmission. We therefore present an improved geometry for optical tapers which offer up to four times the angular tolerance of a lens. The effective area of a photodiode can thus be increased, without decreasing its bandwidth. This makes them suitable for use in our free space QKD experiment and in free space optical communication in general. © Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 201
Keywords: Atmospheric optics; Beam-jitter; Free space communication; Optical taper; Quantum key distribution; Random media

Fading channel estimation for free-space continuous-variable secure quantum communication - Ruppert, Laszlo; Peuntinger, Christian; Heim, Bettina; Günthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique Alexander; Leuchs, Gerd; Filip, Radim; Marquardt, Christoph (New Journal of Physics, 2019)
We investigate estimation of fluctuating channels and its effect on security of continuous-variable quantum key distribution. We propose a novel estimation scheme which is based on the clusterization of the estimated transmittance data. We show that uncertainty about whether the transmittance is fixed or not results in a lower key rate. However, if the total number of measurements is large, one can obtain using our method a key rate similar to the non-fluctuating channel even for highly fluctuating channels. We also verify our theoretical assumptions using experimental data from an atmospheric quantum channel. Our method is therefore promising for secure quantum communication over strongly fluctuating turbulent atmospheric channels.
CRIS-Team WoS Importer:2020-03-06

Free-space propagation of high-dimensional structured optical fields in an urban environment - Lavery, Martin P. J.; Peuntinger, Christian; Günthner, Kevin; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Science Advances, 2017)
Spatially structured optical fields have been used to enhance the functionality of a wide variety of systems that use light for sensing or information transfer. As higher-dimensional modes become a solution of choice in optical systems, it is important to develop channel models that suitably predict the effect of atmospheric turbulence on these modes. We investigate the propagation of a set of orthogonal spatial modes across a free-space channel between two buildings separated by 1.6 km. Given the circular geometry of a common optical lens, the orthogonal mode set we choose to implement is that described by the Laguerre-Gaussian (LG) field equations. Our study focuses on the preservation of phase purity, which is vital for spatial multiplexing and any system requiring full quantum-state tomography. We present experimental data for the modal degradation in a real urban environment and draw a comparison to recognized theoretical predictions of the link. Our findings indicate that adaptations to channel models are required to simulate the effects of atmospheric turbulence placed on high-dimensional structured modes that propagate over a long distance. Our study indicates that with mitigation of vortex splitting, potentially through precorrection techniques, one could overcome the challenges in a real point-to-point free-space channel in an urban environment.
CRIS-Team Scopus Importer:2022-06-05

GAWBS noise reduction in microstructured fibers - Elser, Dominique Alexander; Korn, Alexander; Lorenz, Stefan; Glöckl, Oliver; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (2005 European Quantum Electronics Conference, EQEC '05, 2005)
Guided Acoustic Wave Brillouin Scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. We experimentally demonstrate the reduction of GAWBS noise in microstructured fibers in comparison with standard fibers. © 2005 IEEE.
Created from Fastlane, Scopus look-up

Guided acoustic wave Brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Wittmann, Christoffer; Andersen, Ulrik Lund; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Journal of Physics: Conference Series, 2007)
In silica glass fibers, thermally excited acoustic phonons scatter light into the beam propagating in the forward direction. At acoustic frequencies up to several hundreds of megahertz, the wave vectors of the phonons interacting with the light propagate essentially transversally to the fiber axis. This effect is known as Guided Acoustic Wave Brillouin Scattering (GAWBS) and leads to phase and polarization noise in the guided light. For fiber-based quantum optics experiments, this excess noise is a major limitation. In Photonic Crystal Fibers (PCFs), light is guided by a microstructure simultaneously acting as a 2D transversal phononic crystal which modifies the acoustic noise spectrum. We demonstrate a GAWBS-noise reduction in commercially available PCFs. This gives rise to the prospect of fiber-based quantum optic devices exhibiting less excess noise, thus resulting in higher quantum state purity. Further improvement can be achieved by tailoring the photonic microstructure such that a reduction of phonon noise by design is achieved. © 2007 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Low-threshold optical parametric oscillations in a whispering gallery mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
In whispering gallery mode (WGM) resonator light is guided by continuous total internal reflection along a curved surface. Fabricating such resonators from an optically nonlinear material one takes advantage of their exceptionally high quality factors and small mode volumes to achieve extremely efficient optical frequency conversion. Our analysis of the phase-matching conditions for optical parametric down-conversion (PDC) in a spherical WGM resonator shows their direct relation to the sum rules for photons' angular momenta and predicts a very low parametric oscillation threshold. We realized such an optical parametric oscillator (OPO) based on naturally phase-matched PDC in lithium niobate. We demonstrated a single-mode, strongly nondegenerate OPO with a threshold of 6.7μW and linewidth under 10 MHz. This work demonstrates the remarkable capabilities of WGM-based OPOs. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Naturally phase-matched second-harmonic generation in a whispering-gallery-mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Lassen, M.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
We demonstrate for the first time natural phase matching for optical frequency doubling in a high-Q whispering-gallery-mode resonator made of lithium niobate. A conversion efficiency of 9% is achieved at 30μW in-coupled continuous wave pump power. The observed saturation pump power of 3.2 mW is almost 2 orders of magnitude lower than the state-of-the-art value. This suggests an application of our frequency doubler as a source of nonclassical light requiring only a low-power pump, which easily can be quantum noise limited. Our theoretical analysis of the three-wave mixing in a whispering-gallery-mode resonator provides the relative conversion efficiencies for frequency doubling in various modes. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Naturally phase matched second harmonic generation in a whispering gallery mode resonator - Fürst, Josef; Strekalov, Dmitry; Elser, Dominique Alexander; Lassen, Mikael; Andersen, Ulrik L.; Marquardt, Christoph; Leuchs, Gerd (Lasers and Electro-Optics/Quantum Electronics and Laser Science Conference: 2010 Laser Science to Photonic Applications, CLEO/QELS 2010, 2010)
We observed conversion efficiencies of 9% at 30 μW pump power in LiNbO3, as well as self-limiting effects at high powers. The continuous-wave pump at a wavelength of 1064nm and the second-harmonic feature Q > 107. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Quantum-limited measurements of optical signals from a geostationary satellite - Günthner, Kevin; Khan, Imran; Elser, Dominique Alexander; Stiller, Birgit; Bayraktar, Ömer; Mueller, Christian R.; Saucke, Karen; Troendle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optica, 2017)
The measurement of quantum signals that travel through long distances is fundamentally and technologically interesting. We present quantum-limited coherent measurements of optical signals that are sent from a satellite in geostationary Earth orbit to an optical ground station. We bound the excess noise that the quantum states could have acquired after having propagated 38,600 km through Earth’s gravitational potential, as well as its turbulent atmosphere. Our results indicate that quantum communication is feasible, in principle, in such a scenario, highlighting the possibility of a global quantum key distribution network for secure communication.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (010.1300) Atmospheric propagation; (060.1660) Coherent communications; (060.2605) Free-space optical communication; (270.5565) Quantum communications; (270.5568) Quantum cryptography

Reduction of guided acoustic wave brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Andersen, Ulrik Lund; Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2006)
Guided acoustic wave Brillouin scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. This excess noise affects the performance of various experiments operating at the quantum noise limit. We experimentally demonstrate the reduction of GAWBS noise in a photonic crystal fiber in a broad frequency range by tailoring the acoustic modes using the photonic also as a phononic crystal. We compare the noise spectrum to the one of a standard fiber and observe a tenfold noise reduction in the frequency range up to 200 MHz. Based on our measurement results as well as on numerical simulations, we establish a model for the reduction of GAWBS noise in photonic crystal fibers. © 2006 The American Physical Society.
Created from Fastlane, Scopus look-up

Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication